A PRELIMINARY STUDY ON THE PRAWN FISHERY OF BIG TRAWLERS ALONG THE NORTHEAST COAST OF INDIA - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
The number of big trawlers operating along the northeast coast increasedfrom 55 in 1983-84 to 76 in 1985-86, increasing the prawn landings from 2353 tin 1983-84 to 3043 t in 1985-86. Catch per hour of trawling reached a peak in1984-85 (20.1 kg) and then declined in 1985-86 (16.5 kg). The proportion of'tigers' (8%), 'whites' (30%) and 'browns' (62%) was more or less stable duringthe three-year period.There was a gradual increase in abundance of 'tigers' from 11 m depth to60 m depth and a gradual decrease thereafter. The 'whites' were more abundant in11-40 m depth. The abundance of 'browns' gradually increased from 11 m to 100m depth. There are good fishing grounds in Sandheads I arid off Paradeep andChilka for tigers', off Paradeep, Gopalpur and Kalingapatnam and in SandheadsII for 'whites', off Anchorage, Sunderbans and Gopalpur for 'browns'.The potential yield of prawns from the trawling grounds between Pentakotaand the Sunderbans is estimated at 6559 t. As the present harvest from this regionis 5424 t, there is scope for an addition of 28 more trawlers to the existing fleetof 76.